Data generation for smart hydroponic system development in Syngonium podophyllum (Arrowhead vine) - S.J. Anaswara; M. Rafeekher; P.M. Hasna (JOURNAL OF ROOT CROPS, 2024)
Hydroponics, a young budding science which can be used as an alternative sustainable production system under limited resource availability conditions. High quality ornamental plants can be produced through hydroponics as it encourages faster growth. Arrowhead vine (Syngonium podophyllum) is a widely cultivated ornamental foliage plant as it eliminates polluting agents from inside households. An experiment on standardization of solution culture in Deep Flow Technique (DFT) of hydroponics in Syngonium podophyllum was carried out at College of Agriculture, Vellayani, Thiruvananthapuram during the year 2022. The experiment was laid out in completely randomized design. Four doses of Hoagland solution and cooper solution (50%, 100%, 150% and 200%) were given and replicated ten times. Data on growth parameters for development of a smart hydroponic system was collected in scheduled intervals. The electrical conductivity (EC) and pH were monitored at weekly intervals and observations on growth parameters were taken at every 15 days interval for four months. The treatment with 150% Hoagland solution in Syngonium podophyllum plants showed superior characteristics for number of leaves, leaf length, leaf breadth, plant height and plant spread. The data can be used for developing an automatic hydroponic system controlled by a mobile application and different ornamental foliage plants can be tested using it.